2023
DOI: 10.1007/s11747-022-00921-3
|View full text |Cite
|
Sign up to set email alerts
|

Franchising structure changes and shareholder value: Evidence from store buybacks and refranchising

Abstract: Drawing on agency theory and transaction cost analysis, this study investigates the impact of refranchising and buybacks of downstream retail units by franchising firms on shareholder value (i.e., stock returns). It further evaluates the contingency role of firm and industry factors in shaping this impact. An event study analysis over the years 2001–2020 confirms that both refranchising and buybacks positively affect stock returns. However, notable impact differences emerge between the two types of strategic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…The synergy of big data collection, analytics, and insights capabilities is crucial for achieving high levels of green process innovation. Academic research on innovation has been largely empirical in recent years, with both the business community and academics showing great interest in the topic ( Luu et al, 2023 ; Panda et al, 2023 ; Sørensen et al, 2023 ; Shah & Saqib, 2023 ; Jell-Ojobor, Alon & Windsperger, 2022 ; Hsu & Jang, 2009 ; Sadovnikova, Kacker & Mishra, 2023 ). Paparoidamis et al (2019) found that the degree of innovation in eco-friendly attributes positively affects consumers’ perception of a product’s eco-friendliness and willingness to adopt it.…”
Section: Related Workmentioning
confidence: 99%
“…The synergy of big data collection, analytics, and insights capabilities is crucial for achieving high levels of green process innovation. Academic research on innovation has been largely empirical in recent years, with both the business community and academics showing great interest in the topic ( Luu et al, 2023 ; Panda et al, 2023 ; Sørensen et al, 2023 ; Shah & Saqib, 2023 ; Jell-Ojobor, Alon & Windsperger, 2022 ; Hsu & Jang, 2009 ; Sadovnikova, Kacker & Mishra, 2023 ). Paparoidamis et al (2019) found that the degree of innovation in eco-friendly attributes positively affects consumers’ perception of a product’s eco-friendliness and willingness to adopt it.…”
Section: Related Workmentioning
confidence: 99%